Changes in Bacterial Composition of Zucchini Flowers Exposed to Refrigeration Temperatures. (1st April 2012) - Baruzzi, F.; Cefola, M.; Carito, A.; Vanadia, S.; Calabrese, N.
Abstract : Microbial spoilage is one of the main factors affecting the quality of fresh fruits and vegetables, leading to off-flavor, fermented aroma, and tissue decay. The knowledge of microbial growth kinetics is essential for estimating a correct risk assessment associated with consuming raw vegetables and better managing the development of spoilage microorganisms. This study shows, for the first time, that only a part of total microbial community, originally present on fresh harvested female zucchini flowers, was able to adapt itself to refrigerated conditions. Through the study of microbial growth kinetics it was possible to isolate forty-four strains belonging to twenty-two species of the genera Acinetobacter, Arthrobacter, Bacillus, Enterobacter, Erwinia, Klebsiella, Pantoea, Pseudoclavibacter, Pseudomonas, Serratia, Staphylococcus, and Weissella, suggesting Enterobacteriaceae as potentially responsible for pistil spoilage.